Fabrication of SWNTs/_-Fe2O3 as room-temperature LPG sensor - Buaworn Chaitongrat; Sutichai Chaisitsak (My University, 2015)
A simple fabrication of liquid petroleum gas sensor based on SWNTs/α-Fe 2 O 3 nanocomposite films is reported. SWNTs/α-Fe 2 O 3 films were successfully synthesized through the vertical floating catalyst chemical vapor deposition method using ferrocene-ethanol mist, followed by annealing in air at 350°C to create α-Fe 2 O 3 . To fabricate a sensor, carbon conductive electrodes were directly deposited on top of the SWNTs/α-Fe 2 O 3 films. SWNTs/α-Fe 2 O 3 growth conditions (deposition time and ferrocene/ethanol ratio) were optimized to improve sensor response. The sensor had the capability to detect LPG at a concentration as low as 0.2% LEL (lower explosive limit), indicating possible applications in LPG monitoring at room temperature.
Keywords: Iron oxide chemistry and applications